VD_FINDINFO Arrêt / 2011 / 134 vom 30. November 2010 - VD Tribunal cantonal (2010)
NON-LIEU, MENACEDROIT PÉNAL, PROPAGATION D'UNE MALADIE DE L'HOMME | 180 al. 1 CP, 180 al. 2 let. b CP, 231 CP, 260 CPP, 294 let. f CPP